Parenting Training as a Strategy for Strengthening Children’s Moral Education - Dedi Irama; Emy Herawati (CV. Jalan Cendikia, 2026)
This community service activity aimed to strengthen parents’ capacity to implement parenting practices as a strategy for reinforcing children’s moral education within the family context. The program was based on the need to improve parents’ understanding and skills in developing empathetic communication, parental modelling, positive discipline, and the habituation of honesty, politeness, care, and responsibility. The activity was conducted in October 2022 at a partner school/madrasah and involved 40 parents. It employed a participatory and applicative approach through interactive lectures, group discussions, parenting case simulations, reflective sessions, family action plan development, pre-tests, post-tests, observation, reflection sheets, and limited interviews. The results showed an increase in participants’ understanding, as indicated by the improvement of the average score from 62 in the pre-test to 84 in the post-test. Participants also became more aware of their role as primary educators at home and began formulating practical family routines, including religious habituation, polite communication, age-appropriate responsibilities, parental modelling, and guided use of digital devices. The program also established the “Orang Tua Cinta Akhlak” community as a follow-up forum to support family-school partnerships. Therefore, moral and religious value-based parenting training can serve as an applicative and sustainable model for parental assistance.